Parents' Experiences of Receiving Professional Support Through Extended Home Visits During Pregnancy and Early Childhood—A Phenomenographic Study - Bäckström, Caroline; Thorstensson, Stina; Pihlblad, Jessica; Forsman, Anna-Carin; Larsson, Margaretha (Frontiers in Public Health, 2021)
Background: While becoming a parent can be challenging for all, it can particularly be challenging for those parents and children who are in a vulnerable situation—e.g., in families whose members have problems related to health, relationships, or socioeconomic status. It is essential for health care professionals to identify the more vulnerable families at an early stage. Home visits are one cost-effective way of identifying and supporting such families. This study describes the parental experiences of an intervention that involves professional support in the form of extended home visits. The aim of the study is to describe the parents’ understanding of their experiences of receiving professional support through extended home visits both during pregnancy and the first 15 months of their child’s life. Methods/Design: A phenomenographic approach was used. Semi-structured interviews were conducted with 12 parents who had received the intervention. The interviews were analyzed using the seven-step phenomenography model described by Sjöström and Dahlgren. Results: The following three descriptive categories emerged from the analysis: 1) conceptions concerning the meaning of the physical environment, 2) conceptions concerning extended home visits promoting feelings of self-confidence in the parental role, and 3) conceptions concerning extended home visits promoting parental participation and relations. Conclusion and Clinical Implications: Extended home visits as a form of professional support appear to promote parental self-confidence in parenting ability, giving parents a feeling of security that facilitates conversation with professionals. Children and their entire families had natural roles during home visits, which allowed the children to behave more characteristically. Furthermore, the home visits were understood to facilitate social support through social activities at the child health center as well as integration into Swedish society for migrant parents. Professional support should be adjusted to the unique individual needs of parents, which demands a variety of supportive interventions—for example, reorganizing one or two of the regular clinical visits currently being scheduled as home visits instead.